Why our current embryo experimentation laws are like a medical school toilet - Georgia May (Bioscientifica, 2021)
This essay discusses the uncanny similarities between the toilets at the Leeds School of Medicine and our current regulations on embryo experimentation. Topics touched upon include the reasons behind the establishment of the 14-day rule on embryo culture, why there is a call for an extension to 28 days, and why this may be met with opposition. The author concludes that, much like the toilets at the Worsley building, our current legislation may no longer be fit for purpose and that re-opening the conversation about our 14-day rule is necessary in light of shifting scientific and societal opinion.